(untitled) (Research, Society and Development, 2024)
This article presents a systematic review of the literature on the efficacy and safety of early application of phototherapy in neonates with neonatal jaundice. The aim of the study was to analyze the available scientific evidence to determine whether early intervention offers significant benefits. Methodology: The systematic review followed the PRISMA Guideline. The search used terms such as "neonatal jaundice", "phototherapy", "newborn" and "hyperbilirubinemia" in databases such as Pubmed, Scielo, Cochrane, Embase, Scopus, Lilacs and Web of Science, focusing on articles from the last 10 years. Systematic reviews, case studies, case series, conference abstracts, course conclusion papers, dissertations and theses were excluded, as were studies that included samples of adolescents and adults. Results: Studies have shown that the combination of phototherapy with oral calcium is especially effective, as is the use of different phototherapy devices, albumin infusion and vitamin D supplementation. In addition, intensive phototherapy has been shown to significantly reduce the need for exchange transfusion compared to less intensive methods. Conclusion: Early phototherapy not only reduced the length of hospital stay, but also minimized the need for invasive treatments. Few studies analyzed adverse effects.